1989
DOI: 10.1161/01.str.20.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Morning increase in onset of ischemic stroke.

Abstract: The time of onset of ischemic stroke was determined for 1,167 of 1,273 patients during the collection of data by four academic hospital centers between June 30, 1983, and June 30, 1986. More strokes occurred in awake patients from 10:00 AM to noon than during any other 2-hour interval. The incidence of stroke onset declined steadily during the remainder of the day and early evening. The onset of stroke is least likely to occur in the late evening, before midnight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
224
0
9

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 470 publications
(258 citation statements)
references
References 17 publications
25
224
0
9
Order By: Relevance
“…However, with the advancement and popularity of hospital-based, 24-hour, ambulatory BP monitoring devices as well as homebased self-monitoring devices, the importance of the use of ambulatory BP, especially those measurements taken at home have gained attention (1)(2)(3)(4)(5)(6)(7)(8). HBP obtained early in the morning at home by self-measurement is specifically highlighted as having a substantial impact on cardiovascular risk.…”
Section: State Of Bp Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…However, with the advancement and popularity of hospital-based, 24-hour, ambulatory BP monitoring devices as well as homebased self-monitoring devices, the importance of the use of ambulatory BP, especially those measurements taken at home have gained attention (1)(2)(3)(4)(5)(6)(7)(8). HBP obtained early in the morning at home by self-measurement is specifically highlighted as having a substantial impact on cardiovascular risk.…”
Section: State Of Bp Controlmentioning
confidence: 99%
“…HBP obtained early in the morning at home by self-measurement is specifically highlighted as having a substantial impact on cardiovascular risk. Indeed, many reports indicate a close association between HBP early in the morning and occurrence of cardiovascular events (6)(7)(8)10). In addition, cardiovascular risk is greater in patients with masked hypertension and/or those with poorcontrolled than in those with a well-controlled BP (18).…”
Section: State Of Bp Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…These clinical events lished that pharmacological lowering of BP protects hypertensive patients across a broad age range have a peak incidence in the morning hours as they occur most often between 6 am and noon. [25][26][27][28] In one Summary study of asymptomatic hypertensives with ambulat-BP control has been shown to improve survival and ory ischemia (ST-segment depression) the 24-h to lessen the risk of pressure-related complications ambulatory BP burden was greater in hypertensives in hypertensive patients. However, once the with ambulatory ischemia compared to hypertendecision has been made to initiate antihypertensive sives without transient myocardial ischemia.…”
Section: Timing Of Cvd and MI Clinical Eventsmentioning
confidence: 99%